2013
DOI: 10.1073/pnas.1304291110
|View full text |Cite
|
Sign up to set email alerts
|

Baseline tumor growth and immune control in laboratory mice are significantly influenced by subthermoneutral housing temperature

Abstract: We show here that fundamental aspects of antitumor immunity in mice are significantly influenced by ambient housing temperature. Standard housing temperature for laboratory mice in research facilities is mandated to be between 20-26°C; however, these subthermoneutral temperatures cause mild chronic cold stress, activating thermogenesis to maintain normal body temperature. When stress is alleviated by housing at thermoneutral ambient temperature (30-31°C), we observe a striking reduction in tumor formation, gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
288
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 275 publications
(316 citation statements)
references
References 39 publications
17
288
1
2
Order By: Relevance
“…Housing in relatively cold environments, particularly when animals are individually housed (as is common for cachexia studies), leads to a variety of stress responses and overt changes in inflammation and immune function 66. For example, mice demonstrate altered behavioural and immune responses to lipopolysaccharide and have altered tumour growth and anti‐tumour immune responses when housed in sub‐thermoneutral environments 67, 68. For these reasons, the KPC model was characterized with cage temperatures measured at 26°C and with adequate materials (nestlets) for thermoregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Housing in relatively cold environments, particularly when animals are individually housed (as is common for cachexia studies), leads to a variety of stress responses and overt changes in inflammation and immune function 66. For example, mice demonstrate altered behavioural and immune responses to lipopolysaccharide and have altered tumour growth and anti‐tumour immune responses when housed in sub‐thermoneutral environments 67, 68. For these reasons, the KPC model was characterized with cage temperatures measured at 26°C and with adequate materials (nestlets) for thermoregulation.…”
Section: Discussionmentioning
confidence: 99%
“…We recently compared tumor growth at ST and TT in several syngeneic and carcinogen-induced murine tumor models and found that tumors grow significantly more slowly when mice are housed at TT instead of ST [42]. In addition, spontaneous lung metastases of 4T1 were also significantly reduced in mice at TT.…”
Section: Feeling Cold Tumor Immunology and Therapeutic Efficacy -Nomentioning
confidence: 99%
“…In our experiments, we currently place cages within incubators (Thermo Fisher Scientific) maintained at 228 or 30 8C [42,44,47,48]. We have also used rooms with the temperature set at 228 or 30 8C, but working at 30 o C is indeed uncomfortable for the personnel.…”
Section: Metabol Ismmentioning
confidence: 99%
See 2 more Smart Citations